Soil water extraction by roots and Kc for the coffee crop Extração radicular de água e Kc em cultura de café - Adriana L. da Silva; Isabeli P. Bruno; Klaus Reichardt; Osny O. S. Bacchi; Durval Dourado-Neto; José L. Favarin; Flávio M. P. da Costa; Luis C. Timm (Revista Brasileira de Engenharia Agrícola e Ambiental)
Basic information for a rational soil-water management of the coffee crop is still insufficient, particularly under irrigated conditions. Of great importance for the estimation of water requirements of coffee crops are their root distribuition and evapotranspiration crop coefficients. This study compares soil water extraction by roots of coffee plants of the variety "Catuaí Vermelho" (IAC-44), grown in Piracicaba, SP, Brazil, 3 to 5 years old, with direct measurements of root dry matter, showing a good agreement between both approaches, and confirming that most of the root system is distributed in the top soil layer (0-0.3 m) and that less than 10% of the root system reaches depths greater than 1.0 m. Calculated evapotranspiration crop coefficients are in agreement with those found in the literature, with an average of 1.1, independent of shoot dry matter, plant height and leaf area index. A informação básica para o manejo racional de água e solo na cultura de café ainda é insuficiente, sobretudo em condições de cultura irrigada. A distribuição radicular e os coeficientes de cultura para evapotranspiração são de grande importância para a estimativa da necessidade de água na cultura café. Este estudo compara a extração radicular de água de plantas de café, variedade "Catuaí Vermelho" (IAC-44), cultivado em Piracicaba, SP, Brasil, de 3 a 5 anos de idade, com medidas diretas de material seca de raiz, mostrando boa relação entre as metodologias e confirmando que a maioria do sistema radicular está distribuída na camada superficial de solo (0-0,3 m) e que menos de 10% do sistema radicular atingem profundidades maiores que 1,0 m. Os coeficientes de cultura medidos estão de acordo com aqueles encontrados na literatura, com média de 1,1, independentemente da matéria seca, altura de planta e índice de área foliar.